Aptamer modified Zr-based porphyrinic nanoscale metal–organic frameworks for active-targeted chemo-photodynamic therapy of tumors. Issue 16 (11th April 2023) - Feng, Haidi; Zhao, Lu; Bai, Zhiqiang; Xin, Zhihui; Wang, Chaoyu; Liu, Lizhen; Song, Jinping; Zhang, Haifei; Bai, Yunfeng; Feng, Feng
Abstract : In this work, an aptamer MUC1 modified nanoplatform DOX@PCN@Apt-M was proposed for tumor active-targeted chemo-photodynamic therapy. Abstract : Active-targeted nanoplatforms could specifically target tumors compared to normal cells, making them a promising therapeutic agent. The aptamer is a kind of short DNA or RNA sequence that can specifically bind to target molecules, and could be widely used as the active targeting agents of nanoplatforms to achieve active-targeted therapy of tumors. Herein, an aptamer modified nanoplatform DOX@PCN@Apt-M was designed for active-targeted chemo-photodynamic therapy of tumors. Zr-based porphyrinic nanoscale metal organic framework PCN-224 was synthesized through a one-pot reaction, which could produce cytotoxic 1 O2 for efficient treatment of tumor cells. To improve the therapeutic effect of the tumor, the anticancer drug doxorubicin (DOX) was loaded into PCN-224 to form DOX@PCN-224 for tumor combination therapy. Active-targeted combination therapy achieved by modifying the MUC1 aptamer (Apt-M) onto DOX@PCN-224 surface can not only further reduce the dosage of therapeutic agents, but also reduce their toxic and side effects on normal tissues. In vitro, experimental results indicated that DOX@PCN@Apt-M exhibited enhanced combined therapeutic effect and active targeting efficiency under 808 nm laser irradiation for MCF-7 tumor cells. Based on PCN-224 nanocarriers and aptamer MUC1, this work provides a novel strategy for precisely targeting MCF-7 tumor cells.